ANALISIS OPINI ANGGOTA KOMUNITAS LARI DI KOTA SEMARANG TERKAIT FAKTOR PENYEBAB CEDERA PADA OLAHRAGA LARI - Rinzana Afrah Rohan; Wiga Nurlatifa Romadhoni (UNIB Press, 2025)
This research was conducted to explore the beliefs and perceptions of the members of the Semarang City running community regarding the risk factors contributing to running injuries based on the gender of the community members.The data for this research were obtained using an instrument in the form of a questionnaire.The questionnaire was administered using a Likert scale.The research method used is descriptive with a quantitative approach, with the research subjects being members of the running community in Semarang City.The sample size of this study is 87 active runners, consisting of 59 male runners and 28 female runners.The results of this study indicate that, according to male members, attitude is the highest factor (16.31%) with a very high criterion in causing injuries while running.Meanwhile, female members stated that the biomechanical factor is the highest factor (16.80%) with a very high criterion in causing injuries while running.It can be concluded that there is a difference of opinion among members of the running community in Semarang City regarding the highest factor that can cause injuries in running sports.